Effects of Crystalline Amino Acid Concentrations With or Without Formaldehyde Treatment of Diets on Nursery Pig Growth Performance and Fecal Bacterial Concentration - H. Williams; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband; T. E. Burkey; S. Li (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,235 nursery pigs (PIC 359 × 1050; initially 26.9 lb BW) were used in a 28-d study evaluating the effects of crystalline amino acid concentrations with or without formaldehyde treatment of diets on nursery pig growth performance, feed bacteria concentration, lysine content, and fecal microbial diversity. Sal CURB (Kemin Industries Inc., Des Moines, IA) is a commercial formaldehyde product that is commonly utilized in the poultry industry forSalmonellacontrol in feed but has also been shown to reduce PEDV infectivity in swine diets. Pigs were weaned at approximately 21 d, fed a common starter diet for 10 d, and allotted to pens based on BW in a completely randomized design. Experimental diets were fed in 2 phases (phase 1, d 0 to 12; and phase 2, 12 to 28 post-weaning) in meal form. Experimental treatments were arranged as a 2 × 2 + 1 factorial with main effects of formaldehyde (none vs. 0.30% in all phases) and crystalline AA concentration (low vs. high) plus a positive control. The positive control represented this current production system’s formulated Lys requirement needed to maximize performance, whereas treatment diets were formulated at 80% of the positive control’s lysine concentration. Feed bacterial concentration was determined by performing aerobic plate, Enterobacteriaceae, and total coliform counts on composited feed samples collected from each batch of feed manufactured at the feed mill and directly from feeders at the farm. Total, available, and free Lys analyses were conducted on composited feed samples collected from each phase of the study to determine Lys content. A composite fecal sample was collected from 3 randomly selected pigs per pen on d 28 for each treatment, DNA isolated, and each sample assessed for bacterial community analysis. Overall, a significant crystalline AA × formaldehyde interaction (P<0.05) was observed for ADFI and F/G. The interaction for ADFI was because added formaldehyde in high crystalline AA diets decreased feed intake; however, in low crystalline AA diets, ADFI was unchanged. For F/G, pigs had improved F/G in low crystalline AA diets without formaldehyde, but no difference was observed in high crystalline AA diets. Despite the interaction for ADFI and F/G, formaldehyde-treated diets reduced (P<0.05) ADG, ADFI, and resulted in poorer F/G. Crystalline AA concentration did not impact performance. Added formaldehyde reduced or eliminated bacterial concentration of complete feed in phase 1 of the study. Formaldehyde reduced total and available Lys in both low and high crystalline AA diets, with a greater reduction occurring in low crystalline AA diets, but had no effect on free Lys. Added formaldehyde reduced (P = 0.001) Lactobacillaceae bacterial species, but increased (P = 0.001) Clostridiaceae bacterial species in fecal microbial samples. As expected, formaldehyde treatment reduced bacterial microflora of complete feeds. Overall, the level of crystalline AA did not impact performance while the nursery diet formaldehyde addition negatively influenced growth performance, AA utilization, and fecal microbial diversity.
Keywords: amino acids; formaldehyde; nursery; growth performance